TINJAUAN TINGKAT KESEGARAN JASMANI SISWA SMPN 7 TELUK LATAK KECAMATAN BENGKALIS - Afrizal, Beny; Ramadi, Ramadi; Juita, Ardiah (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
ABSTRACT, Problems in this study is the low physical fitness of students of SMPN 7 Latak Gulf District of Bengkalis, this can be seen in the sport while studying physical education and health, there are still some students who conduct activities are not serious and lazy to do the movements and quickly tired. The research objective was to determine the level of physical fitness of students of SMPN 7 Latak Gulf District of Bengkalis. This research is a descriptive study, conducted on students of SMPN 7. Population is a student of SMPN 7 Latak Gulf District Bengkalis of 13-15 years old and still sits on the class VII, VIII and IX, amounting to 335 people, consisting of 163 men and 172 women. Samples taken from the population by 10% of the population with the withdrawal technique Stratified random sampling prportional totaling 33 people. Data taken with the physical fitness test, which tests physical fitness Indonesia (TKJI) for junior high school students. The data collected were processed using descriptive analysis percentage. From the analysis of descriptive data, the obtained results as follows; physical fitness level female students (58.8%) were moderate. As for the level of physical fitness son (43.75%) were moderate as well.Keywords: physical fitness level